Effect Of Different Housing Systems On Biochemical Parameters In Buffaloes During Winter Season - R. A, Garkal; Kekan , P. M (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
An experiment was conducted to study the effect of different housing systems on biochemical parameters in buffaloes during winter season. Twelve buffaloes were selected and randomly divided into two equal groups. Animals of group – A were housed in shed with net and animals of group – B to shed without net. There was significant (p
Keywords: Housing systems; Biochemical parameters; Buffaloes; cattle